Mit Rechten über Rechte reden. Michael Köhlmeiers Rede vor/zu Rechten und übers Recht: [Talking rightly with the Right about rights. Michael Köhlmeier’s speech before/to the Right and about right] (Studia austriaca, 2019)
Michael Köhlmeier is a speaker for those who lack a voice. This also implies talking to those who are to be blamed for pretending to be mute – and it results in the imperative to take a stand against such a wrong attitude. However, right-wing populism seems to ignore the implications of language; henceforth Köhlmeier has to address them in a way that shows the reasons they refuse to listen: the populists’ inherent lack of responsibility. He shows why he refuses to accept what they do and keeps talking to them because of the difference between the populist and himself, nonetheless offering a dialogue.